DESTINATION BRANDING IN THE BALTIC EUROPE - Studzienicki, Tomasz; Kurjata, Ewa (Acta Scientiarum Polonorum. Oeconomia, 2010)
The process of European integration contributes to creating new tourism destinations. The European Community initiative INTERREG has introduced three strands of co-operation over the borders: transnational, cross-border and interregional. Theoretically, each of these forms of co-operation creates new destinations. These overlap with traditional destinations such as a state, a region and a municipality. The authors are analyzing the case of the Baltic Europe that serves as exemplification of new and old destination branding.